Visual Studio Application for Generation Power System Reliability Calculations - Ikrima Alfi; Rifqi Fauzan Kusmayana (Buletin Ilmiah Sarjana Teknik Elektro, 2023)
Power system reliability is affected by the reliability of its sub-systems, including generator reliability. The reliability of a power plant can be seen, among others, based on the LOLE (Loss of Load Expectation) index. Processing and calculating data using excel or matlab will take a lot of time and effort.  This is unfavorable for system evaluation which is a routine activity. The contribution of this research is to create an easy data processing method with a user-friendly display using Java programming-based Visual Studio. The research data uses generator operating data in 2018 and 2019 Hydroelectric Power Plant Ir. H. Djuanda. Calculations using visual studio have been validated with calculations using Excel. LOLE calculation results in 2018 was 0.17356748092842464 days/year and for 2019 it produced a LOLE of 0.006204969593183424 days/year. The results obtained did not exceed the PLN standard, namely 1 days/year, in other words, in 2018 and 2019 Hydroelectric Power Plant Ir. H. Djuanda has a good level of reliability.